(untitled) (Research, Society and Development, 2021)
Oral mucositis (OM) is one of the main adverse events observed during the treatment of neoplasms, especially in relation to head and neck (H&N) cancer. Complications, initially non-infectious of OM, can significantly compromise the chosen therapy, extend the hospitalization period and decrease the quality of life of patients with H&N cancer. Therefore, the present work presents a narrative review that gathers, presents and discusses studies on the relationship between the topical application of chamomile-based pharmaceutical products and the treatment of oral mucositis, with an emphasis on its effectiveness. A literature search was conducted in August 2021 using PubMed, Scielo and LILACS. From literature search was identified 869 papers, of which 06 were selected to answer the guiding question of this study. Finally, it could be seen that chamomile has great potential to help manage OM, as well as other oral complications, especially in cases of patients undergoing H&N cancer treatments using radiotherapy. Furthermore, formulations containing chamomile have been shown to be effective in slowing the progression of OM grades. However, it is necessary to evaluate in each formulation, the possible impacts of each pharmaceutical adjuvant, as well as the adverse events capable of increasing pharmacotherapeutic adherence.